Exponential stability and stabilization of uncertain T–S fuzzy system with time-varying delay. (2nd April 2016) - Ma, Yuechao; Chen, Menghua; Hu, Xiuling
Abstract: In this article, the problem of exponential stability and stabilization is investigated for Takagi–Sugeno fuzzy time-varying delay systems with parameter uncertainties. Improved conditions are presented in terms of linear matrix inequalities (LMIs). The desired fuzzy controller is obtained by solving these LMIs. In addition, the new integral inequalities can derive less conservative stability criteria. In the end, some numerical simulations are given to illustrate the validity of the proposed methodology.